Quality of Life According to Demographic Characteristics of Patients with Type 2 Diabetes Mellitus - Gladys Coronel Burga; Yely Ranina Sánchez Burga; José Ander Asenjo Alarcón (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Foundation: type 2 diabetes mellitus is a chronic disease that has reached alarming rates of morbidity and mortality in the population. Knowing the quality of life of patients with this condition will allow the execution of plans and contextualized actions. Objective: to determine the quality of life according to demographic characteristics of patients with type 2 diabetes mellitus treated at a provincial hospital in Peru. Methods: a descriptive and cross-sectional study was carried out, carried out between June and August 2022, with 110 patients registered at the Hospital of Chota, Peru. Quality of life was measured with the Diabetes Questionnaire 39, adapted to the context studied. Data analysis was performed with absolute and relative frequencies, 95 % confidence intervals and Mann-Whitney U with p < 0,05 significance. Results: 78.2 % of the patients presented average quality of life at a global level, of which 75 % were men, 81.5 % women, 76.8 % were adults and 82.1 % older adults, in addition, the quality of life was average in diabetes control (92.7 %), anxiety and worry (82.7 %), social overload (65.5 %) and energy and mobility (54.5 %), sexual function was low (85.5 %), the difference in overall quality of life according to sex and age was not significant (p > 0.05), it was only significant in energy and mobility. Conclusion: the quality of life of the patients was average at a global level and by dimensions, the difference in the quality of life of the patients by sex and age was significant in energy and mobility. The planning and establishment of common goals between patients, family members and nursing professionals will allow the achievement of objectives.